O uso da terra e a resposta hidrológica de pequenas bacias em regiões semiáridas - Rodrigues, Joseilson Oliveira (2009)
This work was carried out to evaluate and to compare the hydrologic and sedimentologic behaviour of small rural catchments in the semiarid Northeast of Brazil, as well as to asses the influence of the anthropogenic action over soil and water resources. The study of theses processes is very important for the definition of strategies to a better management of small watersheds and the definition of sustainability plans. The study area is located in the Alto Jaguaribe basin, in the Iguatu County, State of Ceará, Brazil. Four small catchments B1, B2, B3 and B4, neibor to each other, were delimited and equipped with Parshall flumes, water level sensors, rain-gauges and automatic sediment samplers, aiming hydrossedimentologic studies under natural rainfall conditions. In this research, the areas of studied catchments areas are smaller than three ha. In the B1 part of cover vegetation was cut, making it possible to assess the influence of changes in the vegetation cover over runoff, peak discharge and sediment yield. In the others catchments (B2, B3 and B4), cover vegetation was keeping in undisturbed condition, representing the natural condition in the semiarid region of northeast Brazil. The data analysed comprises the hydrologic year of 2009 on the four experimental unities and some events on the months of January, February and March of 2008 on the small catchment B2. Despite the proximity of the monitored unities, the results show high spatial and temporal variability of the hydrossedimentologic answer, and the antecedent soil moisture as the main variable responsible for such modifications. It was observed that lowering the density of the Caatinga vegetation influenced runoff and sediment yield, with greater effects over the first events. Accumulated sediment yield reached values of 1.45, 1.39 and 0.12 ton.ha-1 for the micro-catchments B1, B2 e B4, respectively, at the end of the year 2009. Among all investigated catchments, B3 presented the highest values of runoff and peak discharges, with runoff coefficient average around 28%. The B4 experimental unit had a hydrossedimentologic behaviour very different from the other catchments, showing the lowest values of peak discharge, runoff and sediment yield, and this behaviour can be explained to the soil characteristics. The results presented in this study contribute with important information for the hydrossedimentologic study of semiarid regions, and can be used to guide further research in small catchments with ephemeral regime.